Aortitis as a Rare Cause of Aortic Aneurysm and Valve Regurgitation: Is Repair Precluded? - Carlos Porras; Gemma Sanchez-Espin; Miguel Such; Jesús Sánchez-Ramos; Alicia Bautista-Pavés; Pilar Martín-de la Fuente; Josefa Ruiz; Norberto Ortego-Centeno; Isabel Rodríguez-Bailón; José María Melero (Case Reports in Cardiology)
Aortitis is an infrequent cause of aortic root dilatation and aortic valve regurgitation. Valve-sparing procedures have been proposed, but there is not clear evidence of which is the treatment of choice. We report the case of a 38-year-old pregnant lady with a diagnosis of idiopathic aortitis associated with aortic root aneurysm and severe aortic valve regurgitation.